High Ki67 expression, HER2 overexpression, and low progesterone receptor levels in high-grade DCIS: significant associations with clinical practice implications - Schandiz, Hossein; Farkas, Lorant; Park, Daehoon; Liu, Yan; Andersen, Solveig N.; Sauer, Torill; Geisler, Jürgen (Frontiers in Oncology, 2025)
Simple summaryWe investigated the role of Ki67, a ubiquitous marker in cancer, within the context of ductal carcinoma in situ (DCIS), a precursor of invasive breast cancer. Through rigorous analysis of histopathological and immunopathological samples from a substantial cohort, this study revealed robust correlations between heightened Ki67 expression, diminished progesterone (PR) levels, and HER2 overexpression, indicative of aggressive DCIS phenotypes. These findings offer novel insights into the surrogate immunomolecular subtyping landscape of DCIS, potentially refining risk stratification and therapeutic approaches. This elucidation underscores the translational significance of Ki67 as a prognostic and predictive biomarker in DCIS, with implications for personalized treatment paradigms and patient outcomes.BackgroundThe Ki67 proliferation index is widely used in various tumors, including invasive breast carcinoma (IBC). However, its prognostic utility is often constrained by technical complexity. Its diagnostic and clinical significance in ductal carcinoma in situ (DCIS) remains uncertain. We studied Ki67 immunohistochemistry interobserver diagnostic agreement at different cutoff values in high-grade DCIS. Additionally, we investigated the associations between Ki67 expression, PR levels, and human epidermal growth factor receptor 2 (HER2) in high-grade DCIS among various subtypes (Luminal (Lum) A, LumB HER2-, LumB HER2+, HER2-enriched, and triple-negative)).MethodsUsing histopathological specimens from 484 patients diagnosed with DCIS between 1996 and 2018, we implemented the 2013 St. Gallen recommendations for surrogate immunomolecular subtyping of IBC. Subtypes were classified, and the Ki67 interobserver diagnostic agreement between Counting Pathologist 1 (CP1) and CP2 was calculated using Cohen’s kappa coefficient at various cutoff values.ResultsThe Cohen’s kappa coefficient for interobserver agreement between CP1 and CP2 was κ = 0.586, indicating moderate agreement. Ki67 levels varied significantly among subtypes (p < 0.0001), with a median Ki67% being higher in cases with invasive components (p = 0.0351). Low PR combined with high Ki67% was significantly associated with HER2 overexpression (p = 0.0107).ConclusionsInterobserver agreement for the Ki67 count was moderate. Ki67 expression showed considerable variability in high-grade DCIS. Low PR levels combined with high Ki67 expression were linked to HER2 overexpression, showing possible clinical implications for identifying high-risk DCIS.